Metode Penyusunan Kamus Bahasa Arab: Kajian Teoritis dan Aplikatif - Parida, Asep; Nurlaela, Nurlaela; Tatang, Tatang; Susiawati, Iis (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
Dictionaries play a vital role in Arabic language learning, serving both as linguistic tools and documentation media for language development. This study aims to examine the methods of compiling Arabic dictionaries based on two primary systems: the root-based system (mu’jam q?m?s?) and the alphabetical system (mu’jam hij?’?). Employing a qualitative approach through library research, the study analyzes the characteristics, advantages, and limitations of each method, along with their relevance in modern Arabic instruction. The findings reveal that the root-based system excels in morphological and etymological analysis due to its emphasis on word roots, whereas the alphabetical system offers greater accessibility for modern users by following standard letter sequences. The study also identifies essential dictionary components, such as lemma completeness, phonetic and morphological information, and user-friendly design. These insights contribute to the development of Arabic dictionaries that are both structurally rigorous and pedagogically applicable, particularly for students, educators, and curriculum developers in Arabic language education.